An updated review on surface functionalisation of titanium and its alloys for implants applications - Alipal, J.; Mohd Pu’ad, N.A.S.; Nayan, N. H. M.; Sahari, N.; Abdullah, H. Z.; Idris, M. I.; T. C., Lee (Elsevier, 2021)
Deposition of bioactive and degradable coatings on titanium implants before implantation is objectively to create a biologically-inspired surface that can enhance cell anchorage at the initial stage of implantation and facilitate osseointegration at the later stage of implantation. Therefore, this review paper is aim to discuss the surface functionality of titanium and its alloys regarding its physical structure, chemical composition and biological reaction through its deposited coatings of the altered surface. This review begins by explaining the working fundamentals of biomaterials and present methods used to adjust the titanium surface for biomedical applications, followed by the concept of biocompatibility of the coated surfaces of the titanium-based implant and the mechanism for adapting the affected surface to its bioimplanted environments. The paper also discusses the possible challenges of biocompatibility of the bioactive coating on titanium for implants. Intriguingly, the usability of 3D-printing technology as an implant surface modification technique is addressed in this recent study. In addition to the existing review papers on the surface modification of titanium-based implants, this current review contributes to the outline concept of biocompatible coated titanium. Herein, the outlined principle focused on the osseointegration mechanisms within coated titanium to its implanted environment, most of which are based on recent findings and are further adopted by today’s influential literature on titanium surface modification and its alloys.